Report of the High Level Expert Committee on Efficient Management of Public Expenditure - Planning Commission (Planning Commission, 2011)
The High Level Expert Committee Report on Efficient Management of Public Expenditure (2011) addresses reforms to enhance India’s public financial management framework. The report critiques the traditional Plan vs. Non-Plan distinction, recommending its abolition to enable outcome-based budgeting and integrated expenditure management. Key recommendations include strengthening fund tracking via the Central Plan Scheme Monitoring System (CPSMS) and treasury systems, refining revenue-capital classifications, and bolstering accountability in direct fund transfers. The report emphasizes the strategic role of local bodies, State Public Sector Enterprises (SPSEs), and Public-Private Partnerships (PPPs) in delivering public services and infrastructure. For PPPs, it advocates output-based contracts, risk-sharing mechanisms, annuity ceilings, and Viability Gap Funding (VGF) to encourage private participation while safeguarding fiscal sustainability. Overall, the report proposes a comprehensive, transparent, and accountable framework for managing public expenditure, integrating private sector resources where appropriate, and enhancing efficiency in service delivery and infrastructure development.
Government of India Planning Commission, New Delhi
Government of India Planning Commission, New Delhi
Keywords: Public Expenditure Management; Planning Commission; High Level Expert Committee; Fund Transfers; CPSMS; Revenue-Capital Classification; Treasury Systems; Accountability; Public Sector Enterprises; Public-Private Partnerships; Viability Gap Funding; Annuity Contracts